An Interpretive and Content-Aligned Framework for Urban Entrepreneurship Toward Sustainable Income Generation: Utilizing Thematic Analysis Approach - Karimi Sani, Majid; Bayani, Maryam; Akhavanfar, Amir (Management Strategies and Engineering Sciences, 2025)
In the contemporary era, cities, as primary hubs of economic and social growth, are facing complex challenges in securing sustainable financial resources. Urban entrepreneurship, as an innovative strategy, can bridge individual creativity with collective development, steering cities toward sustainable income generation. The present study aims to design an interpretive and structured framework for urban entrepreneurship geared toward sustainable income generation, utilizing the thematic analysis approach. This research is applied in purpose and descriptive in terms of data collection, conducted with an exploratory approach based on the interpretivist paradigm. The study's participant community comprised university professors specializing in entrepreneurship and urban management, as well as municipal managers from the country's major metropolitan areas. Sampling was carried out using a purposive sampling method, reaching theoretical saturation after 25 interviews. Data collection tools included semi-structured interviews and questionnaires. The findings of this study revealed four overarching themes (infrastructural factors, urban entrepreneurship, sustainable income generation policy, and sustainable income generation), 12 organizing themes (entrepreneurial ecosystem, creative city, policy and urban prosperity, entrepreneurial production conditions, entrepreneurial mindset, entrepreneurial capability, entrepreneurial aspirations, marketing strategy, environmental performance, economic performance, social performance, and sustainable urban economy), and 69 basic themes. To assess the reliability of the identified organizing themes and to explain them within the context of urban entrepreneurship policymaking for sustainable income generation, a fuzzy Delphi analysis was conducted. Based on the evaluation of the first and second phases of the Delphi analysis, all dimensions were confirmed, enabling their assessment through interpretive structural modeling (ISM). Consequently, efforts were made to identify the most influential themes in the urban entrepreneurship policymaking model for sustainable income generation. In analyzing the results, it should be noted that, as indicated in the model, the variables of the entrepreneurial ecosystem, creative city, policy and urban prosperity, and entrepreneurial production conditions were identified as the most impactful themes in the urban entrepreneurship policymaking model for sustainable income generation..